Strengthening Families: Concrete Support in Times of Need - Larry F. Forthun; Samantha Carannante; David C. Diehl (EDIS, 2011)
All families need help sometimes. In times of need, families will often turn to other family members or friends, but some needs may require more concrete financial or material support. This 3-page fact sheet lists many state and local programs that provide concrete support to Florida families who qualify. Written by Larry F. Forthun, Samantha Carannante, and David C. Diehl, and published by the UF Department of Family, Youth and Community Sciences, December 2011.